THE PRECAUTIONARY PRINCIPLE IN THE PRACTICE OF THE HUNGARIAN CONSTITUTIONAL COURT AND CONNECTED AGRICULTURAL INNOVATIONS - István, Dr. Olajos (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Abstract The present article analyses the precautionary principle, which is one of the basic principles determines the basic human behavior applicable to environmental protection. The analysis happens in 3 perspectives. The first is the static perspective, which summarize, what do we mean under the definition of precautionary principle in the environment law. The author separates the precautionary principle from the two other related principles of human behaviour, which are the prevention and the recovery. The second perspective analyses, how this principle can be used in the field of the two areas of agricultural innovations related directly to the environmental protection, which are the food chain and the genetic engineering activities. In this field the question to be examined is, whether the principle is suitable for the corroboration of such bioethics responses that the stem sell of the unborn embryo is usable for saving an other people’s lives. The third perspective is a constitutional change of attitude, the practise of Constitutional Court of Hungary. The main questions are, according to which arguments should integrate the Constitutional Court of Hungary this difficulty interpretable principle for the purpose of the protection of natural resources named as the common heritage of the nation in the Fundamental Law of Hungary and where are the limits of the legal actions regarding this principle. Összefoglaló: A cikk a környezetvédelemben alkalmazható alapvető emberi magatartások alapjait meghatározó egyik alapelvet, az elővigyázatosság elvét elemzi. Az elemzés 3 nézőpontból történik. Az első, statikus nézőpont összefoglalja, mit is értünk az elővigyázatosság elvén a környezetjogban. Az elvet az emberi magatartások másik két kapcsolódó elvétől, a megelőzéstől és a helyreállítástól válassza el a szerző. A második nézőpont azt elemzi, hogyan használható ez az elv a mezőgazdasági innovációk környezetvédelemhez közvetlenül kapcsolódó két területén, az élelmiszerláncban és a géntechnológia tevékenység körében. E körben megvizsgálandó kérdés, hogy alkalmas-e az elv olyan általános bioetikai válaszok alátámasztásaként, hogy felhasználható-e más ember életének megmentéséhez a meg nem született embrió őssejtje. A harmadik nézőpont, egy alkotmányos szemléletváltás- a magyar Alkotmánybíróság gyakorlata. A magyar Alaptörvényben a nemzet közös örökségeként nevesített természeti erőforrások védelmében milyen érvek alapján emeli be ezt a nehezen értelmezhető elvet az Alkotmánybíróság, és hol vannak az elvvel kapcsolatos jogi cselekvés határai.